The specialized parenchyma in the Paspalum vaginatum stem as a strategy to water deficit and salinity - Rebekah Giese de Paula Machado; Alexandra Antunes Mastroberti; Cleusa Bona (Rodriguésia, 2024)
Abstract Paspalum vaginatumis a halophyte plant found along coastal plains, which presents cells with atypically thickened walls in the ground tissue of the stem stele (GTS). The tolerance of this species to high salinity and water stress led us to investigate whether the thickened walls could be related to adaptation to the coastal environment. Thus, we sought to characterize the cell walls that make up the GTS ofP. vaginatum, describe the tissue, and verify the influence of the water resource on the thickening of the walls and a possible function related to the reserve of substances. For this, analyses were carried out using light microscopy, transmission electronic microscopy, and histochemical tests. The samples were collected in the field during low and high rainfall periods.Paspalum vaginatumGTS cells have pectic-cellulosic primary walls. In most basal internodes, these cells presented thickened walls formed in two to three layers. Statistical analysis demonstrated that the level of precipitation is directly related to cell wall thickening. The data suggest the storage and mobilization of substances through the cell wall of the specialized parenchyma.